Donation After Cardiac Death (DCD), Comparative of Scores to Predict Death. (August 2017) - Pugin, D.; Hechinger, S.; Mamjou, H.; Arnaud, E.; Brousoz, S.; Flatres, S.; Freitas, C.; Rennesson, C.; Simon, J.; Moretti, D.; Gasche, Y.
Abstract : Introduction: Prediction of time to death is challenging after withdrawal of life support therapy (WLST), but is requested in patients considered for donation after DCD. In fact, due to medical contingencies and ethical reasons the process should be initiated only if the expected time to death is below 120 minutes. An evaluation tool exists; the University of Wisconsin Donation after Cardiac Death Evaluation Tool1 (UWDCD-ET) which predicts suitability with death occurring, respectively 83.7% within 60' and 74.4% within 120'. A score DCD_N was developed using information available as part of routine medical care to predict death within 60' with a sensitivity and a specificity of respectively 72% and 78%2. The aim of our study is to compare these tools with clinical evaluation by the caregivers to predict death within 60' or 120' of WLST. Methods: We conduct a prospective study between December 2015 and April 2017 in our institution, including all patients where WLST was achieved for the DCD process. The UWDCD-ET, DCD_N and the team prediction (TP), defined as the estimation of probability of death to occur below 60' or 120' by the caregiver, were obtained the day before (D-1) and the same day (D0) of WLST. The gender, age, time to asystole and duration of warm ischemia were also collected. Results: 10 patients were included; all were in a coma with irreversible brain damage. 50% were female and the median age was 55(21-70). 6 patients (60%) died within 60min, 8(80%) died within 120'. 2 patients had a prolonged warm ischemia, which excluded them from organ donation. All patients were extubated in the process of withdrawal of care and were sedated with benzodiazepines, as well as morphine. The prediction for the UWDCD-ET was similar for all measures (D0/D-1 60'/120') with a sensitivity of 100% but a specificity of 50%. These results were very similar to those of the DCD_N score, where sensitivity and specificity were 100% and 66% respectively for the prediction of death within 60'. On the other hand, the team prediction was less accurate for death within 60' (sens 66% spec 0) and slightly improved for prediction at 120' (sens 85 spec 0). Conclusion: Prediction of time to death after WLST based on team prediction is clearly inaccurate. The development of scores to improve the prediction of death seems attractive, but they are of little interest in daily clinical practice being unreliable in identifying patients who will die within the expected time. Due to shortage of organs and until tools to predict death after WLST are improved, each suitable patient should be considered for a DCD procedure. Figure: Patient evolution: DCD: patient is dead within 60'or 120'; Prediction: UWDCD: University of Wisconsin Donation after cardiac death tool; Team: team prediction, DCD_N score valid only for 60'. References: 1. Lewis J, Peltier J, Nelson H, Snyder W, Schneider K, Steinberger D, et al. Development of the University of Wisconsin donation After Cardiac Death Evaluation Tool. Prog Transplant 2003; 13(4): 265-73. 2. Rabinstein AA, Yee AH, Mandrekar J, Fugate JE, de Groot YJ, Kompanje EJ, et al. Prediction of potential for organ donation after cardiac death in patients in neurocritical state: a prospective observational study. Lancet Neurol 2012; 11(5): 414-9. Figure. No caption available.